Organizational culture types, job satisfaction and turnover intentions of employees in four and five star Kota Kinabalu hotels / Dayang Siti Yuzrina Awang Mat Yusof - Awang Mat Yusof, Dayang Siti Yuzrina (2010)
This paper explores the relationship between Organizational Culture Types, Job Satisfaction and Turnover Intentions among employees in four and five star Kota Kinabalu hotels. The dimensions of cultures used in this study are developed by Cameron and Freeman (1991); Clan, Adhocracy, Hierarchy and Market. There are four objectives of the study; to examine the influence of organizational culture types on the level of job satisfaction, to identify which culture type is the strongest contributor towards job, to determine the impact of the job satisfaction level towards turnover intentions and lastly is to investigate the relationship between organizational culture types and the turnover intentions. Eleven hypotheses were outlaid in the study and a single regression analysis using SPSS 16.0 was performed in order to test those hypotheses. The results indicated that the most significant and strongest contributing culture type towards job satisfaction is the Market Culture, followed by Hierarchy, Clan and Adhocracy respectively. Furthermore, the results revealed that indeed job satisfaction significantly influenced the turnover intentions of the hotel employees in Kota Kinabalu. The culture types were found to have a relationship with turnover intentions, and again, the Market Culture was the most significant one out of all the four culture types.